Platelet Reactivity and Early Outcomes after Transfemoral Aortic Valve Implantation - Gross, Lisa; Jochheim, David; Nitschke, Tobias; Baquet, Moritz; Orban, Martin; Holdt, Lesca; Zadrozny, Magda; Hagl, Christian; Teupser, Daniel; Bauer, Axel; Massberg, Steffen; Mehilli, Julinda; Sibbing, Dirk (Thrombosis and Haemostasis, 2018)
Beyond thromboembolic events, peri-procedural bleeding remains one of the most frequent complications after transcatheter aortic valve implantation (TAVI). The majority of TAVI patients receive a dual anti-platelet treatment (DAPT) regimen. This analysis from the EVERY-TAVI register database aimed to analyse whether the level of on-treatment adenosine diphosphate-induced platelet reactivity predicts early outcomes at 30 days after TAVI. A total of 146 consecutive TAVI patients on DAPT who underwent platelet function testing with the Multiplate analyser were included here. Definition of bleeding events was done according to the Valve Academic Research Consortium-2 (VARC-2) classification. In our cohort, a status of low platelet reactivity (LPR, ≤ 18 units) was observed in 79 patients (54%), while high platelet reactivity (HPR, ≥ 46 units) was present in 18 patients (12%). At 30-day follow-up, the incidence of VARC-2 bleeds was 45.6% (n = 36) in LPR patients and 23.9% (n = 16) in patients without LPR (hazard ratio [HR] 2.10, 95% confidence interval [CI], 1.17–3.79; p = 0.01). In age-adjusted multivariate analysis, a status of LPR was independently associated with VARC-2 bleeding events (HRadj, 2.06, 95% CI, 1.14–3.71; p = 0.02). HPR was not associated with the 30-day risk of death, stroke, or myocardial infarction (p ≥ 0.43). In summary, presence of LPR was associated with bleeding events in patients undergoing TAVI while presence of HPR was not associated with ischaemic outcomes at 30 days. The value of platelet function testing for bleeding risk prediction and for a possible guidance of anti-thrombotic treatment in the elderly TAVI population warrants further investigation.
Keywords: transcatheter aortic valve implantation; anti-platelet treatment; bleeding; platelet reactivity; ischaemia